Effects of Botulinum Toxin A Observed During Early Scar Formation Following Rhytidectomy: Controlled, Double-Blinded Pilot Study. Issue 2 (June 2019) - Chambers, Alexandra
Several past studies have suggested there are benefits to using botulinum neurotoxin type A (BoNTA) for improving the aesthetic appearance of established scars. This article describes a study on the prophylactic use of BoNTA for controlling scar formations as they occur. It is based on a small, double-blinded, controlled group of patients having just undergone a facelift procedure. The results suggest that the use of BoNTA just after surgery yield both quantitative and qualitative aesthetic benefits, and the data provide some guidance on optimal doses.